Group portrait of leather men - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows group portrait of leather men outside of Greg's Ballroom on the one year anniversary of the bar. Two men are seated on motorcycles. Three of the men wear sashes indicating their leather title.